2013
DOI: 10.1152/jn.00476.2013
|View full text |Cite
|
Sign up to set email alerts
|

Age-related neuromuscular function and dynamic balance control during slow and fast balance perturbations

Abstract: Piirainen JM, Linnamo V, Cronin NJ, Avela J. Age-related neuromuscular function and dynamic balance control during slow and fast balance perturbations. J Neurophysiol 110: 2557-2562, 2013. First published September 18, 2013 doi:10.1152/jn.00476.2013.-This study investigated age-related differences in dynamic balance control and its connection to reflexes and explosive isometric plantar flexor torque in 19 males (9 Young aged 20 -33 yr, 10 Elderly aged 61-72 yr). Dynamic balance was measured during Slow (15 cm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 34 publications
2
32
1
Order By: Relevance
“…A black mark was fixed on the wall 12.8m from the participant at eye level in order to stabilize the visual focus during the measurements. In the study of Piirainen et al [29] COP maximal displacement in the anterior direction showed the greatest differences between young and elderly participants. This parameter was therefore chosen for further analysis also in the present study and the average of four perturbations was calculated from the anterior direction with the two speeds, fast anterior perturbation (FAP) and slow anterior perturbation (SAP).…”
Section: Methodsmentioning
confidence: 86%
See 2 more Smart Citations
“…A black mark was fixed on the wall 12.8m from the participant at eye level in order to stabilize the visual focus during the measurements. In the study of Piirainen et al [29] COP maximal displacement in the anterior direction showed the greatest differences between young and elderly participants. This parameter was therefore chosen for further analysis also in the present study and the average of four perturbations was calculated from the anterior direction with the two speeds, fast anterior perturbation (FAP) and slow anterior perturbation (SAP).…”
Section: Methodsmentioning
confidence: 86%
“…We deliberately sought to study a wide-ranging sample of ordinary people who were not elite athletes. It has been suggested previously that the control strategy may change during ageing [9] which may lead to different neuromuscular responses during balance perturbations [29]. This may also cause some differences in training adaptations between young and elderly participants, which may explain the quite large variations in dynamic balance control in both pre-and post-tests.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding aging, the work of Piirainen et al (2013) monitored EMG signal of muscles SO, TA and Gastrocnemius of 9 young adults and 10 older adults in the recovery of postural equilibrium after a disturbance in the anterior-posterior and posterioranterior directions. The authors noted that, due to aging a decrease in postural control occurs.…”
Section: Discussionmentioning
confidence: 99%
“…The instrument that was used in this study to measure the balancing abilities of the patient was the balance-measuring instrument (BT-4; Hur Lab, Koarla, Finland), which could evaluate the static and dynamic balancing abilities (Piirainen et al, 2013). The balancing equipment that was used for the test had a 100-Hz sampling rate and a rectangular shape.…”
Section: Methodsmentioning
confidence: 99%